(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to examine organizational culture and its influence on the lifestyle of students at the Darussalam Blokagung Islamic Boarding School. Organizational culture is understood as a system of values, norms, and traditions that guide the behavior of all members of the Islamic boarding school. This study used a qualitative approach with descriptive methods. Data collection techniques included observation, interviews, and documentation studies, while data analysis was conducted interpretively to understand the relationship between organizational culture and the lives of students. The results indicate that the organizational culture at the Darussalam Blokagung Islamic Boarding School is built on strong Islamic values, deep-rooted Islamic boarding school traditions, and exemplary leadership by the kiai (Islamic scholars). The values ​​of sincerity, discipline, obedience, simplicity, and devotion are internalized in the students’ daily lives and form a religious, disciplined, and harmonious lifestyle. This organizational culture significantly influences the development of students’ character, independence, and social adaptability within the community. This study confirms that the organizational culture of Islamic boarding schools plays a strategic role in maintaining the quality of education and the sustainability of Islamic boarding schools amidst the dynamics of modern development. Therefore, strengthening and managing an adaptive organizational culture is an important factor in the development of Islamic boarding school education.